PENGARUH KARAKTERISTIK EKSEKUTIF DAN KEPEMILIKAN KELUARGA PADA TAX AVOIDANCE PERUSAHAAN - Praptidewi, Luh Putu Mayta; Sukartha, I Made (E-Jurnal Akuntansi, 2016)
The purpose of this study is to obtain empirical evidence about the influence of the characteristics of executive and family ownership in the company tax avoidance. The samples in this study using a non-probability samplingdengan purposive sampling performed on companies listed in Indonesia Stock Exchange in 2012-2014. Total samples obtained are 56 companies with 93 of data observations. This study used multiple linear regression analysis. The results of this study show that family ownership a positive effect on tax avoidance, while the executive characteristic negative effect on tax avoidance. This indicates that the higher the lower the characteristics of executive action by the company tax avoidance.
Keywords: Tax Avoidance; Karakteristik Eksekutif; Kepemilikan Keluarga